Slikovni viri in pouk zgodovine - Potočnik, Dragan (Pedagoška obzorja, 2013)
Based on the psychological, pedagical and didactic principles, the history teacher should bring history closer to children by using an approach based on authenticity. One of the most succesful methods to achieve this is working with historical sources, which give the real material foundation for a real understanding of historical facts and phenomena. Among the different historical sources available, visual materials in particular offer a wide variety of uses. Visual sources can be used in all the phases of the period and in all of its forms. For this reason, the study of visual sources has to be an integral part of every period. In using these materials, we have to follow the steps starting with the motive, then using analysis to get a clear image and visual memorisation, and finally reaching a logical conclusion. The importance of visual sources is compounded by the accompanying written sources. These are particularly rich sources conveying a lot of information about the past, the way of living and thinking in a particular historical perriod. Another group of important visual sources includes photographs, posters, caricatures and diagrams.
Keywords: pouk zgodovine; history; zgodovina; učne metode; primary source; zgodovinski viri; slikovni viri